2015
DOI: 10.1111/tbed.12331
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Areas Suitable for the Occurrence of Rift Valley Fever in North Africa: Implications for Surveillance

Abstract: Rift Valley fever (RVF) is a vector-borne zoonotic disease that has caused widespread outbreaks throughout Africa and the Arabian Peninsula, with serious consequences for livestock-based economies and public health. Although there have never been any reports of RVF in Morocco, Algeria, Tunisia and Libya, it is a priority disease in the Maghreb, due to the threat of introduction of the virus through transboundary livestock movements or infected mosquito vectors. However, the implementation of surveillance activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 74 publications
3
46
1
1
Order By: Relevance
“…RVFV causes epizootic outbreaks in tropical areas, mainly in Africa, including Sudan, which is the largest country in Africa [12][13][14][40][41][42]; however, we detected only five infections in adult patients in this study. Another study conducted on 290 patients in eastern Sudan revealed the presence of highly seropositive RVFV IgG [18].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…RVFV causes epizootic outbreaks in tropical areas, mainly in Africa, including Sudan, which is the largest country in Africa [12][13][14][40][41][42]; however, we detected only five infections in adult patients in this study. Another study conducted on 290 patients in eastern Sudan revealed the presence of highly seropositive RVFV IgG [18].…”
Section: Discussioncontrasting
confidence: 70%
“…Dengue, yellow fever, chikungunya, Rift Valley fever, alkhurma haemorrhagic fever, and Sindbis viruses have been reported in more than 34 countries in sub-Saharan Africa and Middle East [10][11][12][13][14]. YFV originated in Africa and spread with the slave trade dating back to at least 1650 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Potential routes of entry of RVFV into Europe and the USA have been identified [22][23][24] and the risk of establishment into North Africa [25], Italy [26], the Netherlands [27] and Spain [28] reviewed. The conclusions collectively identify a need to determine competence in local vectors to accurately evaluate risks, and guide control and surveillance activities [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Not all publications included parameters on the vector, despite all publications investigating VBDs. These publications were focused on transmission in humans and reservoirs [41,42].…”
Section: Models and Modelling Methodsmentioning
confidence: 99%